1996
DOI: 10.1029/96gl02611
|View full text |Cite
|
Sign up to set email alerts
|

Upper atmosphere wind systems during reverse equatorial electrojet events

Abstract: Days of reversed equatorial electrojet were identified at Trivandrum, India, and, in order to seek a global wind change in the dynamo region responsible for these events, upper atmosphere winds at a height of 99 km at Saskatoon, Canada, were examined. During northern winter, and also in April and September, the reversed electrojets were accompanied by reversals of the eastward wind at Saskatoon. The winter events generally occurred during a stratwarm. No changes in the winds were detected during summer reverse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
76
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(81 citation statements)
references
References 15 publications
5
76
0
Order By: Relevance
“…Observational studies have found that the occurrence of CEJ is dependent on the phase of the moon, suggesting that lunar tides play a role (Bartels and Johnston 1940;Rastogi 1974;Sastri and Arora 1981). Other studies found that a large-amplitude CEJ event during winter is often observed during a stratospheric sudden warming event, suggesting a physical connection between the two phenomena (Stening et al 1996;Fejer et al 2010); see Sect. 4.3.3 for more discussion on the stratospheric sudden warming effect on Sq and EEJ.…”
Section: Counter Electrojetmentioning
confidence: 99%
See 2 more Smart Citations
“…Observational studies have found that the occurrence of CEJ is dependent on the phase of the moon, suggesting that lunar tides play a role (Bartels and Johnston 1940;Rastogi 1974;Sastri and Arora 1981). Other studies found that a large-amplitude CEJ event during winter is often observed during a stratospheric sudden warming event, suggesting a physical connection between the two phenomena (Stening et al 1996;Fejer et al 2010); see Sect. 4.3.3 for more discussion on the stratospheric sudden warming effect on Sq and EEJ.…”
Section: Counter Electrojetmentioning
confidence: 99%
“…Early studies hypothesized effects of stratospheric sudden warmings on the ionospheric dynamo (e.g., Brown and Williams 1969;Stening 1977d;Matsushita and Xu 1984;Stening et al 1996;Rastogi 1999). In particular, Stening (1977d) and Stening et al (1996) found that winter-time counter electrojet events tend to occur during stratospheric sudden warmings.…”
Section: Stratospheric Sudden Warming Effectmentioning
confidence: 99%
See 1 more Smart Citation
“…Singh and Cole (1987) incorporated a three-dimensional numerical model that evaluates the role of tidal modes in causing the observed changes in the magnetic field variations associated with the CEJ. Stening et al (1996) suggested that there is an association between CEJ events and high latitude stratospheric warming events. The effect of stratospheric warming on tidal propagation has been reported in the past in a few studies.…”
Section: Introductionmentioning
confidence: 99%
“…The zonal electric field (due to global scale dynamo action), which is responsible for EIA, also causes an intense band of current in the E-region of the equatorial ionosphere known as the equatorial electrojet (EEJ), which generally shows a diurnal pattern with peak amplitudes at local noon. However, even during geomagnetically "quiet" periods, for reasons still being debated (Raghavarao et al, 1980;Somayajulu et al, 1993, Stening et al, 1996, the primary zonal electric field changes its direction from eastward to westward during daytime (Gouin and Mayaud, 1967), which is known as the "Counter Electrojet" (CEJ). Earlier investigations (Raghavarao et al, 1978) revealed that the strength of the EIA has a high degree of cor- The fitted polynomial routine is represented by a solid line, while the width, which is the time interval corresponding to .8 of the maximum intensity, is denoted by the dotted lines in Fig.…”
Section: Introductionmentioning
confidence: 99%